Pemanfaatan Barang Bekas dalam Meningkatkan Kemampuan Motorik Halus Anak - Siti Maghfirah (Institut Agama Islam Negeri Langsa, 2019)
This research aims to improve the children’s fine motor skills by using used goods. The medium was the bottle caps of mineral water that were arranged into various goods of art. The study used a qualitative approach, and implemented the theory of Miles and Huberman in analyzing the data. The data collection techniques used were observation activity, interviews, and documentation. After the research was conducted, found that through the use of media learning goods were very pleasant, not take long, and were innovative and creative in creating the work. The use of media for used goods as a medium of teaching materials emphasize the active role of students in the learning process. Thus, learning not only focuses on teachers but is able to improve the child's fine motor skills through fingers flexibility, as well as the use of their five senses. Researchers concluded that learning activity on the use of media used to improve the children’s fine motor ability, and were able to bring creativity to the child through the activity of sticking the bottle cap into the arrangement of flower petals.